Social-ecological factors associated with loneliness in university students: results from the German cross-sectional StudiBiFra study - Wenig, Vanessa; Heinrichs, Katherina; Heumann, Eileen; Lehnchen, Jennifer; Burian, Julia; Deptolla, Zita; Stock, Christiane (Frontiers in Psychiatry, 2025)
AimsUsing a social-ecological perspective, this study aims to understand loneliness in university students by (1) assessing its prevalence, and (2) identifying inter-personal and organizational factors associated with loneliness during studies.MethodsData from the StudiBiFra study, a cross-sectional survey among university students in Germany, were used. The sample consisted of 12,874 students from 7 universities, surveyed between May 2022 and March 2023 using the Bielefeld Questionnaire on Study Conditions and Mental Health. Hierarchical logistic regression was employed to examine the associations of individual, inter-personal, and organizational variables with loneliness.ResultsA total of 28.2% of students experienced loneliness during their studies. Gender-diverse students (OR = 1.69; 95% CI: 1.04 – 2.73) and males (OR = 1.43; 95% CI: 1.26 – 1.63), as well as those with poor subjective overall health (OR = 2.62; 95% CI: 2.26 – 3.05), were at high risk of feeling lonely. At the inter-personal level, positive social relationships among students acted as a protective factor against loneliness (OR = 0.31; 95% CI: 0.29 – 0.34). At the organizational level, weak connectedness to the university was positively associated with loneliness (OR = 1.43; 95% CI: 1.23 – 1.67), while high university engagement was negatively associated with loneliness (OR = 0.90; 95% CI: 0.83 – 0.97). Students enrolled in universities of applied sciences were less likely to experience loneliness compared to those at universities (OR = 0.76; 95% CI: 0.63 – 0.91).ConclusionsThe findings underscore the importance of both individual and institutional efforts to address loneliness at German universities, a demand that was accelerated during and after the pandemic. Promoting social connections and strengthening students’ ties to their university are important strategies for combating loneliness, highlighting the importance of community-building health promotion.